KONNOTATIONEN DES HEILIGEN IN DER ERÖFFNENDEN STURMSZENE VON GIUSEPPE VERDI’S OTELLO - GOIA, Letiţia; CUTEANU, Cornelia (Studia Universitatis Babes-Bolyai Musica, 2017)
Sacred Connotations in the Opening Storm from Giuseppe Verdi’s Otello. Focusing on Giuseppe Verdi’s adaptation of Shakespeare’s Othello, this paper discusses the usage of the four natural elements – Earth, Air, Water, Fire – and their sacred connotations in the opening storm of Otello. It is common for composers to express key thematic points in the overture or the first scene of an opera and to develop them throughout the entire piece. In adapting William Shakespeare’s play, Verdi chose the tempest in the second act as a starting point for his opera. Thus, The great contention of the sea and skies (Othello, II.1.91) acquires powerful acoustic and visual effects in Verdi’s storm, mirroring Othello’s troubled heart: Flashes! Crashes! Whirlpools! Howling winds and thunder’s mighty roar! Air and water shake together, shaken is the ocean-floor! (Otello, I.1.12-15). Both the opera libretto and the orchestral accompaniment are expressive of the forces of nature which reflect, metaphorically, instances from Othello’s journey through life. Wind, fire, sea, thunder, rocks, lightning, flames – all contribute to offering an insight into what is about to happen. The musical accompaniment is a powerful tool in conveying spirituality, while Shakespeare’s lines resonate in the libretto to the same purpose.